An annotated catalogue of type specimens of the land snail genus Cyclophorus Monfort, 1810 (Caenogastropoda, Cyclophoridae) in the Natural History Museum, London - Nantarat,N. (Pensoft Publishers, 2015)
The collection of land caenogastropod snails in the genus Cyclophorus Monfort, 1810 housed in the Natural History Museum, London (NHM), includes 52 type lots. Lectotypes have been designated for 43 available species-level names to stabilize existing nomenclature, two previously designated lectotype, two holotypes, one paratype, one syntype, one possible syntype and two paralectotypes are also listed. A complete catalogue of the Cyclophorus types in NHM, London is provided for the first time.